Double intussusception in an infant - KIYAN, GÜRSU (W B SAUNDERS CO, 2002)
Intussusception is a common surgical disorder in infancy. Double intussusception (DI), however, is an extremely rare form of this pathology. The authors report a case of idiopathic DI in an 8-month-old girl, which is the third case of idiopathic DI in childhood in the English-language literature. Copyright 2002, Elsevier Science (USA). All rights reserved.
Keywords: intussusception; double; idiopathic